Suggested Regulations to Control Food Supplements - Hadid, Mouyed (Journal of Physical Education, 2011)
The research includes first chapter which has the introduction about athletes and their using food supplements .They think that they run out of food elements. For that reason they use food supplements to substitute what they lost through their exercises and competitions. The researcher explained their balanced diet and what they need. Also found that there are no legislations in most countries to control these supplements. The researcher suggested that food supplements must be controlled by some legislation to avoid any side effect or over dose of using those kinds of food and to be safe of using it